Efeito agudo de distintos protocolos de exercício físico aeróbico sobre biomarcadores plasmáticos e urinários em adultos jovens saudáveis e fisicamente ativos - Daniel Massote Magalhaes (2018)
INTRODUCTION: Physical exercise has been related to physiological adaptations, which improve the physical performance and heathy conditions. Among the possible factors that may contribute to these adaptations is the modulation of biomarkers such as cytokines, adipokines, myokines and renin-angiotensin system components. However, there are scarce data comparing protocols of physical exercise with different intensity in this modulation in active healthy individuals. Therefore, we investigated the acute effect of two iso-work protocols of aerobic exercise in urine and plasma levels of these biomarkers. SUBJECTS AND METHODS: Thirteen young healthy physically active men were recruited to four supervised training sessions. Two evaluation sessions were performed to measure body composition, physical activity, aerobic and anaerobic capacities before High Intensity Interval Exercise (HIIE) and Moderated Intensity Continuous Exercise (MICE) iso-work exercise sessions on a cycle ergometer. The HIIE protocol included a 5-minute warm-up at 60-70% of heart rate peak(HRp) intensity followed by 10 sets of 30 seconds above 90% with 1 minute of recovery and 3 minutes of cool down(both at the same warm-up power). MICE protocol was performed at a constant power corresponding to 60-70% of HRp and finalized at the same total work of HIIE. Blood and urine samples were collected before and after the protocols, then stored at -80°C for further analysis by enzyme-linked immunoassay (ELISA) for RAS components, irisin and adipokines and by the technique of Cytometric Bead Array (CBA) for cytokines. Plasma and urine levels of molecules were measured before (baseline values) and after both exercise protocols. RESULTS: A) We did not find any difference in the comparison of baseline levels (before both exercise protocols) of all cytokines in plasma and urine. On the other hand, we found a significant and positive correlation between plasma levels of TNF and total work in HIIE protocol; B) Irisin and adipokines: Exercise protocols did not change significantly the plasma and urine levels of irisin, leptin, resistin and plasma adiponectin levels. However, urine levels of adiponectin significantly increased after HIIE protocol. C) RAS components: We found following HIIE protocol a significant increase of ACE and Ang (1-7) urine levels and ACE2 plasma levels. Urine concentrations of ACE2 and of Ang-(1-7) significantly raised after MICE protocol. CONCLUSIONS: The HIIE protocol probably improved metabolic profile by increasing adiponectin levels. This protocol stimulated inflammatory response in individuals who pedaled at higher intensities (TNF had a positive correlation with total work in HIIE). In addition, HIIE protocol increased urinary levels of ACE and of Ang-(1-7) and plasma levels of ACE2. However, the MICE protocol was superior to HIIE in increasing urinary levels of ACE2 and Ang (1-7), supporting a beneficial role for cardiovascular and renal adaptations that depend on this pathway.